The Canva Application; Solutions For Development Of Learning Media for Islamic Religious Education at SDN 10 Perembang Gala, Indonesia - Saribujang; Sukino; Erwin Mahrus (IJGIE (International Journal of Graduate of Islamic Education), 2023)
This study aimed to analyze the learning of Islamic Religious Education and BP in elementary schools in an engaging, fun, and not dull learning. This study uses the Research and Development (R&D) research method, and the model used is the ADDIE development model. Media experts have validated this product and tested it with ten students of SD 10 Perembang Gala village of Landau Tubun, Malawi. Primary data sources are Islamic Religious Education teachers, students, and school principals; secondary data sources include research journals, books, and websites. This study's results indicate that the validation results show that media experts get an average of 78.75%, which is included in the "Valid" category of Canva media implementation with links sent via the WhatsApp group for class VI SD Negeri 10 Perembang Gala. The results of student responses to the product average 86.37%, indicating that the product is feasible. The pre-test and post-test results show the effectiveness of developing PAI-BP learning media based on the Canva application, with a score of 100% increasing even though 13.6% has not been completed. Canva application-based media development can increase student motivation and achievement and be used in learning